The Relationship Between Risk Attitudes and Heuristics in Search Tasks: A Laboratory Experiment - Daniel Schunk; Joachim Winter (Ludwig-Maximilians-Universität München, Volkswirtschaftliche Fakultät, 2007)
Experimental studies of search behavior suggest that individuals stop searching earlier than predicted by the optimal, risk-neutral stopping rule. Such behavior could be generated by two different classes of decision rules: rules that are optimal conditional on utility functions departing from risk neutrality, or heuristics derived from limited cognitive processing capacities and satisfycing. To discriminate among these two possibilities, we conduct an experiment that consists of a standard search task as well as a lottery task designed to elicit utility functions. We find that search heuristics are not related to measures of risk aversion, but to measures of loss aversion.
urn:nbn:de:bvb:19-epub-1377-8
Keywords: D83; C91; 330; search; heuristics; utility function elicitation; risk attitudes; prospect theory; Informationsverhalten; Risikofreude; Heuristisches Verfahren; Test; Theorie